Pentingnya Layanan Bimbingan Konseling di Sekolah Dasar Terhadap Perkembangan Peserta Didik - Maryam Qonita; Kristina Betty Artati; Ani Musyarofah; Farah Wahyuni; Awaluddin Tjalla (Guidance : Jurnal Bimbingan dan Konseling, 2022)
This study aims to determine the importance of counseling services in elementary schools on the development of students. This type of research is qualitative. The subjects of this study were elementary school class teachers for small classes 1,2,3 and large classes 4,5,6. The results of the study indicate that: (1) it is felt that it is very important and needed Guidance and counseling services to be applied to primary school education, which are played by BK teachers directly to help students carry out their development tasks, help solve problems/obstacles experienced so that students can grow as individuals with all their needs, can actualize themselves, develop their talents, interests and all their potential (2) As classroom teachers, they still have a role as guidance and counseling teachers and need to continue to improve their knowledge and skills. The skills in assisting and recognizing the characteristics of the needs of each student in the class. (3) It was found that there are many problems or obstacles that arise and are experienced by students in elementary schools, so collaboration and synergy from both the school, class teachers, BK teachers and parents are needed to assist, guide students in completing developmental tasks well.